2017
DOI: 10.1080/1028415x.2016.1277055
|View full text |Cite
|
Sign up to set email alerts
|

Satiety and memory enhancing effects of a high-protein meal depend on the source of protein

Abstract: Results demonstrate the importance of protein source for cognition and satiety enhancing effects of a high-protein meal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…In the present study we repeated a previous finding that meals containing egg white protein induce greater satiety than wheat gluten protein [14] and have further extended this finding to both male and female rats and for both 35% and 20% protein levels. We further showed that the increased satiety from egg white was accompanied by increased postprandial plasma amino acids and lowered respiratory exchange ratio (RER).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the present study we repeated a previous finding that meals containing egg white protein induce greater satiety than wheat gluten protein [14] and have further extended this finding to both male and female rats and for both 35% and 20% protein levels. We further showed that the increased satiety from egg white was accompanied by increased postprandial plasma amino acids and lowered respiratory exchange ratio (RER).…”
Section: Discussionsupporting
confidence: 86%
“…The criteria for the levels of protein used were the following: i) above the recommended amount of protein intake (12-18%) in both humans and rodent diets; ii) 20% protein reflecting the 90th percentile of protein intake within the population and the typical recommended level in high-protein diets in humans, whilst iii) the 35% was included to reflect the upper-limit of high-protein diets in humans [40]. In regards to the other macronutrients, in order to keep the diets isoenergetic changes in levels of protein needed to be paralleled by changes in carbohydrates, keeping the fat levels constant, as previously recommended [14].…”
Section: Experimental Diet Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in food intake after the administration of an equivalent protein dose have previously been reported in the literature. In a study in rats, a high-protein meal composed of egg white suppressed food intake while a wheat-gluten-based meal containing the same percentage of protein, fat, and carbohydrates increased food intake [49]. Other examples are found in the literature for human studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Du et al examined the influence of the protein level and source on Barnes maze performance, satiety and plasma amino acid levels in male rats. Results demonstrate the importance of protein source for cognition and satiety enhancing effects of a high-protein meal [37] (Table 1). Meta-analyses indicate that higher adherence to the Mediterranean diet is associated with better global cognition, episodic memory, lower risk of cognitive impairment and neurodegenerative diseases [38−40].…”
mentioning
confidence: 79%